Interstitial brachytherapy for orbital soft tissue sarcoma: an innovative technique - Siddhartha Laskar; Avinash Pilar; Nehal Khanna; Yogesh Ghadi (Journal of Contemporary Brachytherapy, 2017)
Purpose: To report an innovative technique of interstitial brachytherapy developed for treatment of orbital soft tissue tumors. Material and methods : A 4-month-old child diagnosed with rhabdomyosarcoma of orbit was treated with multiagent chemotherapy (CTh) and brachytherapy. Pre-planning computed tomography (CT) images were obtained and clinical target volume (CTV) was defined using the pre-treatment magnetic resonance imaging (MRI). Brachytherapy plan was generated for deciding optimal catheter placement. With the child under general anesthesia, catheter entry points were extrapolated and marked on the skin as determined from the pre-planning CT scan. Implantation of catheters was performed as per pre-determined catheter position and depths. Brachytherapy plan was generated and evaluated using dose volume histograms (DVH). A comparative external beam radiotherapy (EBRT) plan using RapidArc was also generated for the CTV with a 3 mm margin as the planning target volume (PTV). Results : The mean CTV dose with brachytherapy was 158% compared to 101% with RapidArc. The CTV V100 was 90% for brachytherapy vs. 95% for RapidArc. The mean dose to Lt Lens were 51% and 60%, respectively for brachytherapy and RapidArc, while the corresponding mean doses to the bony orbit were 39% and 68%, respectively. Follow-up MRI at 3 months showed complete response of the tumor. Conclusions : Interstitial brachytherapy for orbit using this innovative technique is a safe and effective modality of local treatment for appropriately selected orbital soft tissue tumors. Brachytherapy resulted in excellent disease control with significant reduction of dose to surrounding ocular structures compared to EBRT.